Beta-Lactamase Resistance Harboured by Escherichia coli isolated from a Dairy Farm - Gray-Hammerton, Charlotte (2023)
CTX-M beta-lactamases have become one of the most prevalent extended spectrum beta-lactamases (ESBL) globally. Their association with mobile elements such as ISEcp1, has allowed for their capture and mobilisation within both human and animal environments. The EVAL farms research programme generated a collection of 1,000 Escherichia coli bovine faecal samples isolated from the environment of a dairy farm on selective media and characterised phenotypically for antibiotic resistance via the disc diffusion method. This current study further characterised the antibiotic resistances of 86 E. coli from the EVAL farms collection, chosen for their beta-lactamase type resistance phenotype. These 86 isolates were grouped according to their resistance phenotypes, which included those suspected of encoding blaCTX-M (reduced susceptibility to ampicillin (AMP), cefotaxime (CTX) and aztreonam (ATM) but susceptibility to amoxicillin-clavulanic acid (AMC) and cefoxitin (FOX)) and those suspected of overexpressing ampC (reduced susceptibility to AMP, AMC, FOX, CTX and ATM. Confirmation of the presence of blaCTX-M by PCR resulted in 39 blaCTX strains being identified and the remaining 47 isolates categorised as putative ampC strains. The presence of an ISEcp1 element was also shown in all blaCTX PCR-positive isolates. The 86 isolates were further characterised phenotypically using minimum inhibitory concentration (MIC) assays via the agar dilution method, with an extended panel of 25 antibiotics which included cefquinome (CFQ). The extended panel included any classes of antibiotics that could cover different resistance mechanisms such as carbapenemases, ESBLs as well as aminoglycoside, tetracycline and colistin resistance. High levels of resistance were seen to AMP, CTX, cefpodoxime (CPD) and CFQ along with resistance to ceftazidime (CAZ), ATM and tetracycline (TET) in the blaCTX isolates. Genotypic characterisation via whole genome sequencing (WGS) was conducted via both short read Illumina and long read MinION Oxford Nanopore Technologies (ONT), with hybrid assembly on all isolates. This WGS was able to show that all the blaCTX-M were of blaCTX-M-15 type, were chromosomally encoded and in association with ISEcp1. WGS also revealed the ISEcp1 element additionally encoded qnrS1 in all isolates and tetAR in 34 of the isolates, with 4 found to contain no tetAR genes and one that had the tetAR genes located separately from the ISEcp1 element, in a different region of the genome. Subsequent in silico multi-locus sequence typing (MLST) using the MLST finder from the Centre for Genomic Epidemiology (CGE), showed all within the blaCTX group to be ST2325. Comparison of the 39 isolates in the blaCTX group by single nucleotide polymorphism (SNP) analysis with 105 ST2325 isolates from the Enterobase database, produced a maximum likelihood tree, showing that the 39 blaCTX EVAL farms isolates were part of their own clonal branch of the tree and within 1-5 SNPs of each other, demonstrating that spread of blaCTX-M-15 on this dairy farm was likely as a result of clonal expansion. Other ST2325 isolates from Enterobase were found not to be closely related to the 39 blaCTX isolates, with the closest an E. coli bovine isolate from Spain which was within 36-45 SNPs of the 39 blaCTX isolates. It was also noted that ST2325 isolates from other published studies analysed from Enterobase appeared to form separate clonal study-associated clusters, with clonal groups of ST2325 within 0-6 SNPs of each other. The use of WGS allowed resistance genes to be identified and compared to the phenotypic data, and plasmids and other mobile elements including the ISEcp1 elements to be characterised. The potential for ISEcp1 to mobilise a chromosomally-encoded blaCTX-M-15 to a resident plasmid and transpose to another strain and whether sub-lethal levels of antibiotics used in dairy farming (including AMP, cloxacillin (CLOX) and CAZ) might enhance this transposition of ISEcp1, was addressed through transposition experiments with four isolates from the blaCTX group. The sub-lethal levels of these antibiotics used, looked to mimic the concentrations that might be encountered by bacteria of treated animals or within the environment of the dairy farm. Transposition of the ISEcp1 element in association with blaCTX-M-15, was successful with all concentrations of AMP, CLOX and CAZ and enhanced transposition with an increased rate of transfer (when compared to the baseline rate of transfer in non-selective media) was successful with some concentrations of AMP, CLOX and CAZ. Levels of enhancement varied from 1.07 fold to 45 fold the baseline rate. The characterisation of subsequent transconjugants encoding ISEcp1 elements using WGS via both Illumina short and MinION (ONT) long read with hybrid assembly showed that the ISEcp1 elements could either lose or gain downstream genes, through the recognition of a new imperfect IRR site. This revealed a possible mechanism for the loss or gain of a phenotype within the dairy farm E. coli isolates. Isolates of the second group of E. coli displaying a beta-lactamase type phenotype, the ampC group, when further characterised through MIC assays showed that many phenotypic resistances indicated by the disc assay were lost and only four of the 47 isolates in the ampC group were resistant to streptomycin (STREP), six were resistant to TET and only one isolate was resistant to trimethoprim/sulfamethoxazole combination (SXT). Only 22 isolates were showing likely overexpression of ampC according to the MIC assay results, with high level resistance to AMP along with resistance to CAZ, CPD and ATM with intermediate resistance to CTX. Through a combination of both PCR and Sanger sequencing, and WGS, 22 isolates were confirmed as overexpressing ampC by locating mutations in the promoter regions of ampC. WGS of the 47 isolates in the ampC group identified additional resistance genes including beta-lactamase type resistance genes blaTEM-1 and blaOXA-1 in one isolate each respectively, mobile genetic elements (MGEs) and a small number of virulence genes. MLST typing showed, 21 isolates were ST1308 with 20 of these overexpressing ampC. These 21 ST1308 were subject to SNP analysis via snippy and a maximum likelihood tree was constructed. From these data it appeared the earliest sampled isolate, which was not overexpressing ampC, was within 431-561 SNPs of the remaining 20 ST1308 isolates and therefore was not closely related but did appear to share a common ancestor them. Within the remaining 20, 19 were within 5-1 SNPs of each other and one was within 8-16 SNPs of those 19. Therefore, it appeared the 19 were likely clonal and the 1 within 8-16 SNPs appeared to be very closely related to those 19. This suggested that in this particular dairy farm environment, there had been a small clonal expansion of isolates of the same ST, with the majority also encoding overexpression of ampC. The results of this study showed a potential mechanism for mobility of blaCTX-M-15 within the environment of a dairy farm, demonstrated there had been spread of blaCTX-M-15 as a result of the clonal expansion of ST2325 and also revealed several different mechanisms in place for beta-lactamase type resistance including both blaCTX-M-15 and overexpression of ampC. The study also showed the benefits of utilising both phenotypic and genotypic methods together for the identification of resistance mechanisms within E. coli.